Conspirator : foreigner #10 - Cherryh, C. J. (Cherryh, C. J. Foreigner universe., 2009)
Cajeiri, the young son of the powerful leader of the Western Association, has become a target for forces bent on destroying his father's rule. For Cajeiri is the first "ateva" youth to have lived in a human environment and the first of his people to ever truly understand the so similar--yet so dangerously different--aliens who share his home planet and threaten the hidebound customs of his race.